PENGARUH PENERAPAN PEMBELAJARAN KONTEKSTUAL TERADAP HASIL BELAJAR TEMATIK SISWA KELAS V - Asniah, Nur; Sabri, Tahmid; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe purpose of this article is to prove the effectiveness of the application of contextual learning on the thematic learning outcomes of fifth-grade students of North Pontianak 07 primary school. This study uses a quasi-experimental method with a Nonequivalent control group design. The study population was all grade 5 students of North Pontianak 07 Elementary School. Based on the result of data analysis, the average post-test in the experimental class was 76.40, while the control class was 70.79. The result of the hypothesis test using a t-test (Polled variance) with DK 47 at a significant level of 5% known t_ (table) = 2.014 then obtained t_ (count) = 2.254. Therefore Ha is accepted and Ho is rejected. It can be concluded that there is a difference in the result of the post-test scores of students in the experimental class with the control class. it means that there is an effect of the application of contextual learning to the thematic learning outcomes of fifth-grade students of North Pontianak 07 Elementary School. The result of the calculation of the effect size of student learning outcomes in the experimental class and the control class was 0.46. Based on the effect size criteria can be categorized in the medium category, it means that the application of contextual learning has a moderate effect on the thematic learning outcomes of students in class V of North Pontianak 07 Primary School.Keywords: Contextual, Influencer, Thematic